1993
DOI: 10.1152/ajpgi.1993.264.6.g1031
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent regulation of cholecystokinin secretion and potassium currents in STC-1 cells

Abstract: Secretory and electrophysiological properties of STC-1 cells, a cholecystokinin-secreting cell line, were examined with a radioimmunoassay and patch-clamp recording techniques. Stimulation of cholecystokinin secretion was seen after exposure to agents anticipated to increase the level of intracellular calcium, including thapsigargin (8 microM), bombesin (50 nM), potassium-induced depolarization (50 mM), or after blockade of potassium channels with barium chloride (2 mM). The secretory effects of these agents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…This conclusion is consistent with our in vivo immunohistochemical studies indicating that gut L cells, like gut K cells, do not express detectable Kir 6.1 or Kir 6.2. Patch-clamp studies have also demonstrated the presence of K ATP channels in parent STC-1 cells (2,28,30,58). Thus it has been proposed that they play a role in regulating CCK secretion (2,27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is consistent with our in vivo immunohistochemical studies indicating that gut L cells, like gut K cells, do not express detectable Kir 6.1 or Kir 6.2. Patch-clamp studies have also demonstrated the presence of K ATP channels in parent STC-1 cells (2,28,30,58). Thus it has been proposed that they play a role in regulating CCK secretion (2,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…All cells were cultured in an atmosphere of 5% CO2-95% air and 100% humidity. MIN6 cells (passage [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] were cultured in DMEM containing 15% FCS, as previously described (39,67), and GIP/Ins cells were cultured in DMEM containing 10% FCS (39).…”
Section: Methodsmentioning
confidence: 99%
“…ATP-sensitive K ϩ channels regulating basal membrane potential (20,23) can be affected by CaSR. However, there was no difference in basal secretion between CaSR WT and KO CCK-eGFP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several physiological secretagogues (such as monitor peptide and amino acids) as well as exposure to depolarizing concentrations of KCl increase [Ca 2+ ] i , which is linked to hormone release (7,8,23,24). In this study, involvement of calcium signaling in ILDR1-stimulated CCK secretion was demonstrated by comparing [Ca 2+ ] i in wild-type and Ildr1 -/-CCK-EGFP cells.…”
Section: Figurementioning
confidence: 85%
“…Changes in intracellular calcium concentrations are critically important for regulated CCK secretion (23,24). Figure 6), suggesting that these cells were capable of responding to amino acid stimulation.…”
Section: Figurementioning
confidence: 99%